The Interhemispheric Fissure: A Commonly Mislabeled Cranial Landmark - Jeanty, Philippe; Romero, Roberto; Crelin, Edmund; Hobbins, John C. (American Journal of Perinatology, 1985)
The bright midline echo observed in fetal cranial sonography has been termed by many authors the “falx cerebri.” Anatomic, embryologic, and sonographic evidence presented here suggests that this terminology is incorrect and that use of the term “interhemispheric fissure” is more appropriate.